Predictors of anxiety in early-stage Parkinson's disease – Results from the first two years of a prospective cohort study. (October 2017) - Rutten, Sonja; van der Ven, Peter M.; Weintraub, Daniel; Pontone, Gregory M.; Leentjens, Albert F.G.; Berendse, Henk W.; van der Werf, Ysbrand D.; van den Heuvel, Odile A.
Abstract: Aim: Anxiety has a negative impact on daily functioning and quality of life in patients with Parkinson's disease (PD). This study aims at assessing which sociodemographic and clinical characteristics predict the course of anxiety in early PD. Methods: The participants of this two-year prospective cohort study were recently diagnosed PD patients not receiving psychiatric medications or dopamine replacement therapy at baseline. Assessments were performed annually after baseline. The primary outcome measure was anxiety, as measured with the State-Trait Anxiety Inventory (STAI). Covariates were age, gender, family history, striatal dopamine transporter binding ratios, and severity of motor and non-motor features of PD at baseline. Data were analyzed using a mixed model analysis. Results: Inclusion criteria were met by 306 subjects. An increase in STAI total score was predicted by older age, lower score on the Montreal Cognitive Assessment, and the presence of a probable REM-sleep behavior disorder (RBD) at baseline. A decrease in STAI total score over time was predicted by a higher baseline score on the 15-item Geriatric Depression Scale, compulsive behavior at baseline and a family history of PD. Conclusions: More severe baseline anxiety was associated with compulsive behavior and depressive symptoms. These symptoms had a parallel course, showing a decrease over time. An increase in anxiety was predicted by older age, worse cognitive functioning and the presence of RBD. Our findings, when replicated in a sample of PD patients in a more advanced disease stage, could provide starting points for prevention of anxiety in PD patients. Highlights: We assessed predictors for the course of anxiety in patients with early-stage Parkinson's disease. Symptoms of anxiety, depression and compulsive behavior showed a parallel course. An increase of anxiety was predicted by age, cognitive functioning and REM-sleep behavior disorder.